2011
DOI: 10.1007/s11738-010-0706-4
|View full text |Cite
|
Sign up to set email alerts
|

Stem girdling influences concentrations of endogenous cytokinins and abscisic acid in relation to leaf senescence in cotton

Abstract: Many studies have shown that root-shoot imbalance influences vegetative growth and development of cotton (Gossypium hirsutum L.), but few have examined changes in leaf senescence and endogenous hormones due to stem girdling. The objective of this study was to determine the correlation between some endogenous phytohormones, particularly cytokinins and abscisic acid (ABA), and leaf senescence following stem girdling. Field-grown cotton plants were girdled on the main stem 5 days after squaring (DAS), while the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 62 publications
3
16
0
Order By: Relevance
“…Leaf cytokinin content was increased in fruit-removal plants but decreased in girdled plants; in contrast, the ABA content was decreased in fruit removal plants and increased in girdled plants [6], [52]. Our previous results also suggested that the cotton line, K1 senescence earlier than K2 due to its lower cytokinin and higher ABA contents [19], [52].…”
Section: Introductionmentioning
confidence: 70%
See 2 more Smart Citations
“…Leaf cytokinin content was increased in fruit-removal plants but decreased in girdled plants; in contrast, the ABA content was decreased in fruit removal plants and increased in girdled plants [6], [52]. Our previous results also suggested that the cotton line, K1 senescence earlier than K2 due to its lower cytokinin and higher ABA contents [19], [52].…”
Section: Introductionmentioning
confidence: 70%
“…Our previous results also suggested that the cotton line, K1 senescence earlier than K2 due to its lower cytokinin and higher ABA contents [19], [52]. Although studies have indicated possible correlation of leaf senescence with cytokinins and ABA in cotton [6], [19], [52], the expression profiles of senescence-related genes, particularly hormone related and TF genes and their involvement in senescence regulation in cotton have not been documented. In the present study, we compared the difference between the transcriptomes of main-stem leaves obtained from an early senescence (K1) and a late senescence (K2) cotton using the Solexa sequencing system during leaf senescence.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…So in our study, obstruction of mineral nutrients from roots to leaves may another reason for leaf senescence in girdled A. sparsifolia. In addition, stem girdling interrupts phloem transport of acropetal flow of cytokinin (Kong et al 2011), thus reduced levels of cytokinin which subsequently resulted in the acceleration of leaf senescence (Dai and Dong 2011). So induced senescence may also regulated by the change of phytohormones (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Leaf senescence is induced by numerous factors, such as darkness (Buchanan-Wollaston and others 2005; Gregersen and others 2013), high light intensity (Fu and others 2012), high light dosage (Gregersen and others 2013;Noodén and others 1997), heat (Gregersen and others 2013;Lobell and others 2012), water stress (Yang and others 2003), nitrogen starvation (Koeslin-Findeklee and others 2014), salicylic acid (SA) (Vogelmann and others 2012), abscisic acid (ABA) (Gregersen and others 2013;Setter and others 1980), jasmonic acid (JA) (Jiang and others 2014), cytokinins (Zwack and others 2013), carbon famine (Brouquisse and others 2001;Parrott and others 2005), carbon feast (Moore and others 2003;Parrott and others 2005), and disease (Gregersen and others 2013;Robert-Seilaniantz and others 2011). Many experiments have shown that girdling can cause leaf carbohydrate accumulation and accelerate the senescence process (Krapp and Stitt 1995;Parrott and others 2007), girdling accumulates carbohydrates such as soluble sugar and starch, which cannot be expelled from source organs (leaf), which subsequently causes the accumulation of carbohydrates above the girdle (Dai and Dong 2011;Nebauer and others 2011;Rivas and others 2006;Roper and Williams 1989;Urban and Alphonsout 2007;Yang and others 2013) and results in the carbon feast-induced senescence in leaves (Parrott and others 2005;Parrott and others 2010;Parrott and others 2007).…”
Section: Introductionmentioning
confidence: 99%